PENGARUH PERTUMBUHAN PERUSAHAAN, FINANCIAL DISTRESS DAN REPUTASI AUDITOR TERHADAP PERGANTIAN KANTOR AKUNTAN PUBLIK - Suharto, - (2019)
This research was conducted to examine the effect of variable The Company Growth, Financial distress and Firm Reputation to the possibility of Substitution Public Accounting Firm (KAP) at manufacturing industry are listed in them Indonesia Stock Exchange during 2011 to 2013. The Population in this study amounted 144 companies manufacturing industry listed on the Indonesia Stock Exchange during 2011 to 2013. The samples obtained in this study is 126 companies selected using purposive sampling method. Data were tested using logistic regression method using the t-statistic with a confidence level of 5%. The results showed that the variable of Company Growth and Financial distress are not significant effect on the possibility of turnover Public Accounting Firm (KAP), while the variable of Firm Reputation is significant effect on the possibility of turnover Publick Accounting Firm (KAP).